Implementasi Pendekatan Etnomatematika Untuk Meningkatkan Motivasi Dan Hasil Belajar Matematika Siswa Kelas V - Sholihin, Adnan; Faudati, Mirva; Septiyanti, Isnani F.; Dewi, Novi A.K; Irfan, Muhammad (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This research aims to increase students' motivation and learning outcomes in Mathematics through the application of an ethnomathematics approach. The subjects of this research were 10 students from one of the elementary schools in Kapanewon Samigaluh, Kulon Progo Regency, consisting of 6 boys and 4 girls. The research uses classroom action research methods. The research results show an increase in student motivation and learning outcomes in each cycle. In the first cycle, student motivation in understanding the concepts of KPK and FPB reached 61% and was included in the good category. In cycle II, there was an increase in student motivation in understanding the concepts of KPK and FPB to 82% in the very good category. Furthermore, the completeness of students' Mathematics learning outcomes in cycle I reached 60% with an average score of 69.4. In cycle II, there was an increase in the completeness of students' Mathematics learning outcomes to 80% with an average score of 78.3. Based on these findings, it can be concluded that students' motivation and learning outcomes in Mathematics are improved through the application of an ethnomathematics approach.